Intercultural Adaptation Individu Kecamatan Bandar dengan Pendatang dari Host Culture yang Berbeda - Firmanda, M. Alvino; Telasih, Tutut Rahayu; Prathama, Nikolaus Ageng (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
The purpose of this study is to describe the causes behind the process of cultural shock occurrence with the process of adjustment when the arrival of new people who bring culture of origin and then communicate with the host culture that causes intercultural adaptation in the area around Diponegoro University Campus K. Rod. This research uses a descriptive qualitative approach. The data sources obtained in this study are from interviews,observations,and data collection (written sources). The subject of the study was citizens around campus locations and students who came from different host cultures. The informant selection technique used is purposive sampling technique. Data validity technique using source triangulation techniques. Data Analysis Techniques use interactive analysis models consisting of data collection, data analysis, data presentation, and conclusion withdrawal. This research shows the process of adapting communication between host culture by bringing the culture of origin that resulted in culture shock.